Coupling the Charging Current and the Electron‐Transfer Process: The Effect on Impedance Spectra. Issue 1 (6th October 2016) - Du, Guoqing; Mantia, Fabio La
Abstract: By using a 1D simulation of the charge‐transfer process, taking into account the nature of the electron‐tunnelling and the effect of the electric field in the double layer, we analysed the coupling between double layer charging and faradaic reaction and assessed how this influences the shape of impedance spectra simulated under equilibrium conditions for a redox couple. We carried out the simulations with different concentrations of redox couple and supporting electrolyte at different equilibrium potential. We observed that, independent of the conditions of the simulation, all the data sets could be fitted by a simple Randles circuit. Our results show that the coupling process of faradaic and charging currents is manifested as a deviation of the behaviour of the charge transfer and interface differential capacitance from the expected values; in particular, we show that the electric field affects very strongly the charge transfer resistance, and also that the charge accumulated on the double layer is affected by the electron‐transfer. Abstract : No frequency dispersion : Simulations of impedance spectra for the electron‐transfer process reveal that the coupling of charging and faradaic currents does not cause a time constant distribution; however, the values of the charge transfer resistance and differential capacitance are affected by the Frumkin effect and by electron tunnelling.